THE RESEARCH ON ANTICIPATION OF VESSEL CAPTAINS BY THE SPACE OF KELLY’S GRAPH - Nosov, Pavlo; Popovych, Ihor; Zinchenko, Serhii; Cherniavskyi, Vasyl; Plokhikh, Viktor; Nosova, Halyna (Revista Inclusiones, 2020)
The paper examines the issue of identifying anticipation of ship captains in critical situations. The purpose of the study is to develop a fundamentally new formal approach to create a map of captains’ negative anticipation in order to prevent disastrous consequences on maritime transport caused by a human factor. To achieve the purpose of the study the following steps were taken: we examined the principles of the systemic approach conforming to the concept of the methodology of an individual’s expectations and the levels of formalization; determined the components of an elementary formal and mathematical system within the framework of the approach under study; formulated the order of structural principles of creating the model of an individual’s anticipation in the form of axioms. The experiment using the maritime navigation simulator Transas navigation simulator NTPRO 5000 made it possible to present a captain’s behavior as Kelly’s graph allowing us to identify the points of manifestation of his anticipation. The research also determined the correlation of these points and changes in technical parameters of the trajectory of a ship route confirming the research hypothesis.